Constructing Human Versus Non-Human Climate Migration in the Anthropocene: The Case of Migrating Polar Bears in Nunavut, Canada. Issue 1 (27th May 2020) - Reid, Julian
Critical anthropology is currently awash with research aimed at disabling human exceptionalism, alignment with indigenous knowledge, decolonisation of thought, and the taking of the posthuman turn. Meanwhile states with settler colonial histories, such as Canada, also seek to align policies with indigenous knowledge and seek reconciliation with indigenous peoples. This article examines this trend by analyzing the conflict occurring in Nunavut between the Canadian state and Inuit communities living there, over the migration of polar bears. In this context, indigenous knowledge clashes with the rationalities and policies of the state. Claiming support from biological science, the state argues that the migration of the bears indicates their threatened status, while the Inuit argues it to be an expression of polar bear resilience. What does this clash of rationalities tell us about the integrity of the posthuman turn, given that its legitimacy depends on claims of alignment with indigenous knowledge and interests as well as opposition to western science and colonial state power? States with colonial histories, including Canada, as well as international organisations including the United Nations, are at pains these days to stress the extent to which their policy responses to the climate crisis are informed by indigenous knowledge. However, the construction of indigenous knowledge in the policies of colonial states, as much as in critical anthropology, is rendered problematic by the analysis offered in this article. Were Inuit knowledge and perspectives on the climate migration of polar bears to be taken seriously, different policies and different approaches, based on the privileging of the human over and against the interests of the animal would have to prevail.